Kajian Teoretis Tentang Pendidikan Multikultural dan Pendekatan Implementasinya di Indonesia - Musron; Nur Istianah; Asiyah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study discusses multicultural education theories and approaches as a response to the increasing social complexity resulting from cultural, ethnic, religious, and linguistic diversity in modern societies, particularly in Indonesia. Multicultural education is a strategic solution in building a tolerant, fair, and inclusive society through a learning process that respects differences and upholds equality. This study uses a qualitative method with a library research approach, utilizing various academic literature sources such as books, journal articles, and official documents to examine multicultural education theories in depth. The analysis was conducted descriptively and analytically to examine the main concepts of thinkers such as James A. Banks, Sonia Nieto, Christine Sleeter, Carl Grant, H.A.R. Tilaar, and Parsudi Suparlan. The results of the study show that Banks' theory focuses on five dimensions of multicultural education, Nieto emphasizes critical aspects and social justice, while Sleeter and Grant offer a classification of contextual approaches. From an Islamic perspective, multicultural education is rooted in the values of tawhid, justice, ukhuwah, tasamuh, and ta'āruf as reflected in the Qur'an and Hadith. In conclusion, the implementation of multicultural education in Indonesia requires synergy between the curriculum, pedagogical strategies, school culture, and community involvement to create a humanistic and civilized education system in accordance with the values of Pancasila and Islam. This study contributes by systematizing theoretical perspectives and presenting an integrated conceptual framework that can serve as a reference for curriculum development and policy formulation on multicultural education in Indonesia.